Regional Head Election During COVID-19 Pandemic: the Antinomy in the Government Policies - Rizki Ramadani; Farah Syah Rezah (Universitas Airlangga, 2021)
Welcoming the simultaneous regional head election in 2020, it is expected to be an entry point in building a higher quality democracy in Indonesia. Initially, this year's election should be held on September 23. However, this plan must be constrained when the coronavirus disease 2019 (COVID-19) outbreak occurs and spread wildly all over the world including Indonesia, and was officially declared a pandemic by World Health Organization (WHO). When the number of positive cases and deaths continues to increase, the government decided to continue holding the regional election in the midst of the pandemic. Such policy created controversy and faced several challenges, especially regarding the government's inconsistency in fulfilling the rights of its people in the time of the pandemic. This article aims to explain and analyze the contradiction in the government policies from the antinomy of law and human rights perspective. This legal research is doctrinal research conducted using a conceptual, statutory, and case approach. The data will be described in a descriptive-prescriptive manner through qualitative analysis. The results of the analysis show that there are some contradictions between policies regarding physical distancing (both in the Large-Scale Social Restrictions (PSBB) and Health Protocol regulations) and the policy for holding Regional Head Elections during the pandemic. In essence, this contradiction is the antinomy between the aspects of public health and political rights. Antinomies occur when the government seeks to fulfill and guarantee political rights as well as public rights to health at the same time during a pandemic, which actually leads to mutual negation between these rights.